Correction: Mutations in LRRK2 linked to Parkinson disease sequester Rab8a to damaged lysosomes and regulate transferrin-mediated iron uptake in microglia. - Adamantios Mamais (PLoS Biology, 2022)
[This corrects the article DOI: 10.1371/journal.pbio.3001480.].